The impact of obesity on psoriasis - Dorota Krasowska; Michał Adamczyk (Termedia Publishing House, 2016)
Many psoriatic patients, especially those suffering from severe forms of the disease, are obese and present other features of metabolic syndrome. It is likely due to proinflammatory activity of hormones and cytokines, called adipokines, which are produced by excess of fat tissue. Obese psoriatic patients usually have more severe skin lesions. They also respond poorly to systemic antipsoriatic therapies. Furthermore, this group of patients has a higher frequency of cardiovascular events and metabolic complications as well as psychological disturbances, such as depression, low self-esteem and anxiety disorders. Dietary counseling and lifestyle modification aimed at weight loss should be an integral part of therapeutic management in obese patients with psoriasis.